Keberhasilan Pertumbuhan Stek dan Hasil Bunga Krisan Varietas Puspita Nusantara Akibat Pemberian Dosis Pupuk Kandang Sapi dan Konsentrasi Auksin - Lia Amalia; Wahyono Widodo; Anne Berliana; Iis Aisyah; Ai Komariah; Odang Hidayat; Nunung Sondari (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
The availability of nutrients and growth hormones will affect plant growth and yield. Experiments to study the effect of the interaction between cow manure dose and auxin concentration on the success of cuttings growth, growth and yield of Puspita Nusantara chrysanthemum flowers were carried out. The experimental design used was a factorial randomized block design. There are two treatment factors that were repeated 2 times. The first factor is the dose of manure consisting of four levels of 0 t ha-1, 10 t ha-1, 20 t ha-1, and 30 t ha-1. The second factor is the auxin concentration consisting of four levels, namely 0 ml L-1 solution, 1.3 ml L-1 solution, 2.6 ml L-1 solution and 3.9 ml L-1 solution. The results showed that there was an interaction between cow manure dose and auxin concentration on the number of leaves, stem diameter, number of flower buds, flower diameter, flower stalk length, and vaselife. Independently, the dose of cow manure 20 t ha—1, 30 t ha-1 and auxin concentration of 2.6 ml L-1 , 3.9 ml L-1 solution gave higher plant height than the control.